HOPE AND PEER ATTACHMENT AS PREDICTORS OF RESILIENCE IN S1 UNIVERSITY STUDENTS IN THE SPECIAL REGION OF YOGYAKARTA - Nahdatul Fitri; Yulia Ayriza (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
Resilience is a critical psychological capacity that enables individuals, particularly students, to recover from various stressors and challenges. Students with low resilience tend to be more vulnerable to stress and less capable of adapting to life’s adversities. Previous research has demonstrated that both hope and peer attachment individually influence resilience. Therefore, this study aims to investigate the role of hope and peer attachment as predictors of resilience both jointly and individually among undergraduate students enrolled in universities in the Special Region of Yogyakarta (DIY). This study employed a quantitative approach with a survey research design. The research was conducted at several universities across the DIY, involving 393 undergraduate students selected through incidental sampling. Data were collected using three standardized instruments: (1) the Brief Resilience Scale (BRS); (2) the Hope Scale developed by Snyder; and (3) the Inventory of Parent and Peer Attachment (IPPA) by Armsden and Greenberg. The content validity of all instruments was confirmed using the Gregory formula, with each instrument scoring a value of 1.00. Reliability testing indicated acceptable to excellent internal consistency, with Cronbach’s Alpha values of 0.661 for the BRS, 0.933 for the Hope Scale, and 0.931 for the IPPA. The data were analyzed using descriptive statistics and multiple linear regression, performed with SPSS version 25. The results of the study indicate that: (1) hope and peer attachment jointly serve as significant predictors of resilience among undergraduate students in the Special Region of Yogyakarta, with an F value of 80.369 and a significance level of α = 0.000 (p < 0.05); (2) hope is a significant individual predictor of resilience, with a T value of 10.471 and α = 0.000 (p < 0.05); and (3) peer attachment is also a significant predictor, with a T value of 9.410 and α = 0.000 (p < 0.05). The combined contribution of hope and peer attachment to resilience is 29.2%, with hope accounting for 21.9% and peer attachment accounting for 18.5% of the variance in resilience.